Estimating the extent and economic impact of under and overdiagnosis of chronic obstructive pulmonary disease in primary care. (August 2016) - Spyratos, Dionisios; Chloros, Diamantis; Michalopoulou, Dionisia; Sichletidis, Lazaros
The aim of the present study was to estimate the frequency of under- and over-diagnosis as well as overtreatment and their impact on the financial burden of inhaled drugs for stable chronic obstructive pulmonary disease (COPD). We examined 3200 subjects (65.5% males) of the general population (>40 year old, current or former smokers, and asthma patients were excluded) during a 3-year period. All participants gave detailed medical history, underwent spirometry, and their current and past inhaled medications were registered through the national electronic prescription system. We diagnosed 342 subjects (10.7%) with COPD of whom 180 (52.6%) had no prior medical diagnosis. Overdiagnosis was the case for 306 subjects (9.6%) of whom 35.1% were treated with inhaled drugs during the last year. We calculated that 55.4% of the current cost for inhaled drugs is wasted to overtreatment and overdiagnosis. If there was adherence to Global Initiative for Chronic Obstructive Lung Disease (GOLD) guidelines both for the diagnosis and treatment it would be a net profit of 36, 059€ annually, which would be increased to 116, 017€ if we had excluded underdiagnosed patients. Under- and over-diagnosis of COPD as well as non-adherence to GOLD guidelines for treatment are common problems in the primary care setting that increase significantly the economic burden of inhaled medications.